(untitled) (World Bulletin of Management and Law, 2024)
This article is devoted to the analysis of key problems associated with the recognition of evidence as admissible or inadmissible in criminal proceedings. The author explores the essential criteria and legal nature of the property of admissibility of evidence. The author analyzed legislation and scientific material on the issue of admissibility and inadmissibility of evidence in the national and foreign aspects of the study